The Advent of Scientific Aircraft Navigation - Barata, Jorge M M (2022)
Two Portuguese aerial navigators, Gago Coutinho and Sacadura Cabral, crossed for the first time, from Europe to the South Atlantic in 1922; they developed and used for the first time scientific methods of astronomic navigation when flying out of sight of land: a path corrector and a precision sextant. Both navigation devices were tested during short flights from Lisbon to Madeira Island (1921) and the encouraging results obtained, allow the navigators to apply them with quite success into an intercontinental flight. The “path corrector” was invented by Sacadura Cabral and Gago Coutinho with the intent to calculate graphically the angle between the longitudinal axis of an airplane and the direction of flight, taking into account the intensity and the direction of the winds. The regular sextant used by the navy could not be applied to aviation due to the difficulty of the definition of the sky-line at a normal flight altitude. Gago Coutinho developed a new model of sextant that could be used to measure the altitude of a star without the need of the sea horizon; this new device was called “precision sextant” and was improved with an artificial horizon line defined with the help of a water bubble. This device was later improved with an internal illumination system to allow its use during night flights and was used along the First Aerial South Atlantic Night Crossing, in 1927, performed by Portuguese airmen Sarmento Beires, Jorge Castilho, Duvalle Portugal and Manuel Gouveia. An advanced version of this instrument started to be manufactured in Germany by C. Plath under the name of “System Admiral Gago Coutinho”.